Mechanism of Action Potential Prolongation During Metabolic Inhibition in the Whole Rabbit Heart - Mačianskienė, Regina; Martišienė, Irma; Navalinskas, Antanas; Treinys, Rimantas; Andriulė, Inga; Jurevičius, Jonas (Frontiers in Physiology, 2018)
Myocardial ischaemia is associated with significant changes in action potential (AP) duration, which has a biphasic response to metabolic inhibition. Here we investigated the mechanism of initial AP prolongation in whole Langendorff-perfused rabbit heart. We used glass-microelectrodes to record APs transmurally. Simultaneously, optical AP, calcium transient (CaT), intracellular pH and magnesium concentration changes were recorded using fluorescent dyes. The fluorescence signals were recorded using an EMCCD camera equipped with emission filters; excitation was induced by LEDs. We demonstrated that metabolic inhibition by FCCP resulted in AP shortening preceded by an initial prolongation and that there were no important differences in such response throughout the wall of the heart and in the apical/basal direction. AP prolongation was reduced by blocking the ICaL and Ito with diltiazem and 4 aminopyridine, respectively. FCCP induced a reduction in CaTs and intracellular pH and increased intracellular Mg2+ concentration. Also, resting potential depolarisation was observed, which clearly indicates a decrease in the inward rectifier K+ current (IK1) that can retard AP repolarization. Thus, we suggest that the main currents responsible for AP prolongation during metabolic inhibition are the ICaL, Ito, and IK1, the activities of which are modulated mainly by changes in intracellular ATP, calcium, magnesium, and pH.